Opportunities, Challenges, and the Urgent Role of Guidance and Counseling in the ASEAN Economic Community (AEC) Era - Fini Alfionita Umar; Annas Salahudin (Indonesian Journal of Guidance and Counseling Studies, 2025)
Background: The ASEAN Economic Community (AEC) integrates 10 Southeast Asian countries, creating a competitive market that requires students to develop skills and readiness. Guidance and counseling in schools are crucial to support students’ career development in this dynamic environment. Objective: To determine the urgency of guidance and counseling in the ASEAN Economic Community (AEC) era. Method: Literature review with searches for scientific journal articles on Google, Google Scholar, and ResearchGate. Result: The AEC is one of the largest markets in Southeast Asia, involving 10 countries. Guidance and counseling play a crucial role in addressing challenges arising from the AEC through (1) enhancing students' self-efficacy, (2) brief solution-focused counseling, and (3) guidance and counseling services to prepare a high-quality AEC workforce. Conclusion: Guidance and counseling are essential in overcoming challenges posed by the implementation of the AEC. Contribution: This study provides theoretical and practical scientific knowledge on the role of guidance and counseling in the AEC era, offering research novelty.